EFEKTIFITAS GAYA KEPEMIMPINAN CAMAT DI KECAMATAN CIDADAP KOTA BANDUNG - Doli Tua Mulia Raja Panjaitan; Dearma Sariani Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2019)
This thesis describes a leadership style effectiveness by the head county of Cidadap Bandung. The research was conducted in Cidadap Subdistricts Office in Bandung and the samples are all of the county of Cidadap Bandung subordinate. The research title of this thesis is “Leadership Style Effectiveness of Head County Cidadap in Bandung”. The purpose of this research is to describe how effective the leadership style which have been used by the head county of Cidadap Bandung. The type of the research is using Descriptive. Data collection technique is using Questionnaire filled by respondent which are 24 in number and supported by Interview. Data analysis was done by using descriptive analysis which type is average for leadership style analysis and frequency distribution for leadership situation analysis and leadership style effectiveness analysis. The research result shows that effectiveness of the Sub-district Leadership Style belongs to the ineffective category.